2019
DOI: 10.1101/839134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellular life from the three domains and viruses are transcriptionally active in a hypersaline desert community

Abstract: SummaryMicrobial communities play essential roles in the biosphere and understanding the mechanisms underlying their functional adaptations to environmental conditions is critical for predicting their behavior. This aspect of microbiome function has not been well characterized in natural high-salt environments. To address this knowledge gap, and to build a general framework of relating the genomic and transcriptomic components in a microbiome, we performed a meta-omic survey of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Viruses have also been studied in hypersaline Atacama environments; Crits-Christoph et al (29) identified viral sequences and their potential hosts in halite endoliths. Additionally, Uritskiy et al (30) detected transcriptionally active viruses potentially infecting Halobacteria also inhabiting halite salt nodules in a salar located in the Atacama Desert. These niche halite host-virus relationships highlight the need to characterize the impact of viruses in broad desert soils that represent one of the largest and rapidly expanding terrestrial ecosystems on the planet (~35% of the Earth's land surface (31)).…”
Section: Introductionmentioning
confidence: 99%
“…Viruses have also been studied in hypersaline Atacama environments; Crits-Christoph et al (29) identified viral sequences and their potential hosts in halite endoliths. Additionally, Uritskiy et al (30) detected transcriptionally active viruses potentially infecting Halobacteria also inhabiting halite salt nodules in a salar located in the Atacama Desert. These niche halite host-virus relationships highlight the need to characterize the impact of viruses in broad desert soils that represent one of the largest and rapidly expanding terrestrial ecosystems on the planet (~35% of the Earth's land surface (31)).…”
Section: Introductionmentioning
confidence: 99%
“…We obtained 10 to 100 ng of RNA/g of grounded halite. RT-PCR was used to validate the absence of contaminating DNA in the total RNA used for RNA-seq libraries with 16S rRNA primers 515F/926R (18).…”
Section: Methodsmentioning
confidence: 99%
“…Whole-genome sequencing libraries were prepared using the KAPA HyperPlus kit (Roche) as previously described (14) and sequenced with paired 150-bp reads on the HiSeq 2000 platform at the Johns Hopkins Genetic Resources Core Facility (GRCF). Total RNA-seq libraries were prepared with the SMARTer Stranded RNA-seq kit (38), using 25 ng of RNA input and 12 cycles for library amplification, as previously described (18). We sequenced 21 libraries from replicate samples from 2016 and 24 libraries from replicate samples from 2017 (see Table S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations